The Effect of Chewing Gum on Acceleration of hospitalized time stay among Post-Cesarean Section Patients At Kendari City Hospital - Andi Herman; Safaruddin Admad (International Journal of Nursing and Health Services (IJNHS), 2021)
Cesarean section (CS) is the most significant surgical intervention that affects the central nervous system and slows down the bowel movement after CS. Intervention in the early period after CS is needed to improved bowel function. This study aimed to determine the effect of chewing gum on the acceleration of hospitalized time among post-cesarean section patients at  Dewi Sartika Public Hospital. This quasi-experimental study was conducted with 72 patients divided into two groups of such as 36 for the intervention group, and 36 were the control group at Dewi Sartika Public Hospital. For data analysis, A paired T-test was used to describe the mean difference before and after receiving the intervention among the intervention group and the control group. After the 3-day intervention, there was a significant acceleration of hospitalization time in the intervention group (P<0.05) compared to before the intervention. Chewing gum is an effective intervention in accelerating the number of days of stay in post-cesarean section patients